PENGELOLAAN HUBUNGAN SEKOLAH DENGAN MASYRAKAT DI SEKOLAH DASAR NEGERI KECAMATAN KOTO TANGAH KOTA PADANG - April Yona Dwieka Sari (Jurnal Bahana Manajemen Pendidikan, 2015)
The purpose of the research is to gather information about (1) planning (2) organizing (3) actuating (4) controlling of public relations. The population are 57 and sample are 37 elementary school headmasters in Kecamatan Koto Tangah. The instrument of this research is questioner using Likert scale models that have been tested. The data analyze trough average score. The result of this research show that management of public relations of the elementary school in Koto Tangah, Padang is good with overall score 4,07.